2021
DOI: 10.1590/1984-3143-ar2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged use of letrozole causes morphological changes on gonads in Galea spixii

Abstract: Letrozole is used as a therapeutic agent in reproductive disorders caused by high estrogen levels. Letrozole inhibits cytochrome P450 aromatase and reduces estrogen levels. However, the effects of longterm use on reproductive traits are unknown. The aim of this study was to evaluate the prolonged use of letrozole in the gonads of rodents (Spix's yellow-toothed cavy; Galea spixii). Forty-eight rodents (24 males and 24 females) were randomly divided into the treated and control groups. Letrozole administration s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…This finding is in complete agreement with the previous study in which letrozole-induced animals showed weight gain, similar to those associated with PCOS in women. 22 Comparable results were also reported in other studies where Letrozole-induced PCOS rats showed more weight gain than control animals. 23,24 The increased weight gain in PCOS animals or human beings could be due to elevated levels of circulatory androgen which results in hunger and increased food intake.…”
Section: Discussionsupporting
confidence: 74%
“…This finding is in complete agreement with the previous study in which letrozole-induced animals showed weight gain, similar to those associated with PCOS in women. 22 Comparable results were also reported in other studies where Letrozole-induced PCOS rats showed more weight gain than control animals. 23,24 The increased weight gain in PCOS animals or human beings could be due to elevated levels of circulatory androgen which results in hunger and increased food intake.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, the imbalance of testosterone/estradiol levels by the long-term letrozole treatment can cause a reverse effect in treated animals. Prolongated letrozole use was reported to delay the development of seminiferous tubules and spermatogenesis (Maria Angelica Machado Arroyo et al, 2021). In addition, higher testosterone levels can completely sterilize the animal, as reported by several studies in mammals and fishes (Solar and Donaldson, 1985;Vanderstichel et al, 2015), which was not observed in our case.…”
Section: Discussionsupporting
confidence: 69%
“…In testis, aromatase inhibition and, hence, estrogen deficiency demonstrated a direct influence on the morphology of seminiferous tubules and interstitial tissue in mice (Kondarewicz et al, 2011). The imbalance of steroidal hormones can cause testis tissue abnormalities in prolonged treatment of letrozole (Arroyo et al, 2021;Pilutin et al, 2014). The increase in the estradiol levels can promote Leydig cell hypertrophy and hyperplasia and increase inflammatory cell numbers in transgenic mice expressing high aromatase levels (Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that there is a linear relationship between the local estrogen produced by spermatozoa and sperm capacitation and acrosome reaction, and the synthesis of estrogen in spermatozoa may affect its fertilization ability 50 . Arroyo et al's research 51 also has similar views. Their team found through rat experiments that the long‐term use of LE could lead to the reduction of estrogen, resulting in changes in reproductive characteristics and ultimately infertility.…”
Section: Discussionmentioning
confidence: 88%